The breeding behavior of Glyphoglossus molossus and the tadpoles of Glyphoglossus molossus and Calluella guttulata (Microhylidae) - Altig, Ronald; Rowley, Jodi J.l. (Zootaxa, 2014)
The breeding behavior of Glyphoglossus molossus is described from still and video images taken in Cambodia. These large, burrowing frogs follow the general theme of microhylids that deposit aquatic eggs: explosive breeding in ephemeral water and performing multiple amplectic dips to oviposit surface films of pigmented eggs. A portion of a clutch is released with each dip, a dip lasts for about 6 s, 200-300 eggs are released per dip, and about 5 s pass between dips. The ova have a dark black animal pole and yellow vegetal pole. Expanded datasets on the morphology of the tadpoles of Glyphoglossus from Vietnam and Calluella from Myanmar are presented.